Effect of pozzolanic industrial wastes on durability of engineered cementitious composites (ECC) - Ferdosian, I. (2017)
In this research 26 different compositions of an engineered cementitious composite with different percentages of Fly ash and Silica fume, as two pozzolanic industrial waste and by-product, were mixed. The effect of different percentage of the pozzolans on durability of ECC was studied. To evaluate the durability of the material, two tests, namely water absorption by immersion and water absorption by capillary, were performed. The results from both tests demonstrated the same trend regarding the influence of the wastes on durability. In other words, by increasing the amount of pozzolans, the water absorption after immersion and boiling, decreased more than 50% besides the significant reduction in the rate of absorption by capillary (sorptivity). The results also indicated that silica fume has a higher influence on the water-absorption reduction compared to fly ash however, in the case of absence of silica fume, fly ash plays a significant role on the improvement of durability of the material.